The Distribution of the Agentive Nominalizer of the Suffixes -er and -an - Karlina Denistia; Francis Borgias Alip (Universitas Sanata Dharma, 2014)
This study focuses on the suffixes er and -an because these suffixes are the most commonly used suffixes in daily life and thus really productive. There are three problems formulated for this topic: (1) What are the characteristics of stems receiving suffixes er and -an? (2) What meanings are introduced by suffixes er and an? (3) What are the distributions of the allomorphs of suffixes er and -an? The data of this study are morphemes and affixes. Hornbys Oxford Advanced Learners Dictionary (year of 2000) is used. Finally, the present researcher found that the suffixes er and an are attached to certain verbs, adjectives, and nouns. The suffix -an are not attached to verbs. The suffix -er is mostly attached to transitive verbs to create three possibilities of meaning. There is only one meaning of the suffix er when it is attached to an adjective, and eight meanings of the suffix er when it is attached to certain nouns. For suffix -an, there are three meanings when it is attached to adjectives and five meanings when it is attached to nouns. There are two meanings of the suffix -an when it is attached to nouns. The allomorph of the suffix -er are or, -eer /??r/, and ier /??r/, while the allomorphs of the suffix -an are ian /?n/, -ian /??n/, and ean /??n/. Keywords: morpheme, derivational suffixes, an agentive nominalization, stem, allomorph